PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA WAHANA SURYA BENGKULU - Muhammad Galy Njoman Ari Prabowo; Furqonti Ranidiah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThe purpose of this study was to determine the effect of job satisfaction and organizational commitment on employee performance at Wahana Surya Bengkulu.The object of this research was Wahana Surya Bengkulu with the selection of samples in this study conducted by using total sampling. The number of respondents in this study were 65 respondents. The data collection method uses questionnaire.The results of the study show that The first, there is a positive effect of job satisfaction toward the employees’ performance of  Wahana Surya Bengkulu, if the ability is getting better or improved, there is a positive influence of work organization commitment toward the employees; performance of Wahana Surya Bengkulu, if the work discipline of employees increases, it will affect the performance of employees of Wahana Surya Bengkulu,  if employee work motivation increases, of course employee performance will also increase in line with increasing employee motivation, there are effects of job satisfaction, organizational commitment on the performance of employees of Wahana Surya Bengkulu employees, where job satisfaction and organizational commitment affect performance by 61.4%Keywords: Job Satisfaction, Organizational Commitment,  Performance